2020
DOI: 10.3390/rel11110577
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Short Forms of Centrality of Religiosity Scale in Russia

Abstract: Since the end of the Soviet Union, Christian Orthodoxy has regained importance in Russian society. Considering the religious dynamics in the decades after 1990, scholars working in the field have been debating about a reliable measuring tool for religiosity. The present study provides a validation of two short forms of the Centrality of Religiosity Scale (CRS), the CRS-5, and CRSi-7 in Russia, as well as its corresponding translated items. Therefore, data from two large-scale sociological surveys from 2008 (N … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Although the Abrahamic forms of the CRS have been validated and applied in numerous studies, it is still noteworthy to look at its current validations from different religious and sociocultural contexts. Ackert et al (2020a) validated the short forms of CRS in Russia and concluded that the CRS-5 is suitable for the Orthodox-dominated religious landscape. Esperandio et al (2019) validated the Brazilian version CRS-10BR and CRS-5BR and concluded that the CRS-10BR captures the CRS full construct.…”
Section: The Centrality Of Religiosity Scale: Various Forms and Appli...mentioning
confidence: 93%
“…Although the Abrahamic forms of the CRS have been validated and applied in numerous studies, it is still noteworthy to look at its current validations from different religious and sociocultural contexts. Ackert et al (2020a) validated the short forms of CRS in Russia and concluded that the CRS-5 is suitable for the Orthodox-dominated religious landscape. Esperandio et al (2019) validated the Brazilian version CRS-10BR and CRS-5BR and concluded that the CRS-10BR captures the CRS full construct.…”
Section: The Centrality Of Religiosity Scale: Various Forms and Appli...mentioning
confidence: 93%
“…Thus, the CRS five core dimensions were generally constructed such that they could be found in many different religious cultures. Indeed, past studies (Ackert et al 2020a(Ackert et al , 2020bdel Castillo et al 2020;Demmrich 2020;Esperandio et al 2019;Lee and Kuang 2020;Huber and Huber 2012;Huber and Krech 2009;Ju et al 2018;Stanford and Jong 2019) also reported empirical evidence for these core dimensions in many different religions and cultures. Of particular relevance are the studies by Ju et al (2018) and Stanford and Jong (2019).…”
Section: Introductionmentioning
confidence: 95%
“…The CRS is widely used in various studies related to religiosity (e.g., some recent publications, Zarzycka et al 2020;Riegel 2020;Ackert et al 2020aAckert et al , 2020bEsperandio et al 2019;Huza 2018;Fradelos et al 2018). The Centrality of Religiosity Scale has a comprehensive and economic way of assessing personal religiosity by including the dimensions associated with ideology, intellect, religious experience, private, and public religious practices.…”
Section: Instruments and Analysesmentioning
confidence: 99%
“…The CRS has undergone confirmatory factor analyses many times in different linguistic and cultural contexts (some recent examples: e.g., Esperandio et al 2019;Huza 2018;Ackert et al 2020aAckert et al , 2020b. In Huza's case, the CRS-15 was tested in Romania with 4 different confessions (Orthodox, Catholic, Pentecostal, and Seventh-day Adventist), whereby the Orthodox element comprised 68% of the total sample (n = 215).…”
Section: Confirmatory Factor Analysesmentioning
confidence: 99%
See 1 more Smart Citation